Rapid diagnostic test versus microscopy in the diagnosis of acute malaria in a district hospital in Enugu state, Southeast Nigeria - Umegbolu, Emmanuel I.; Madukwe, Chinedu N. (International Journal Of Community Medicine And Public Health, 2017)
Background: Malaria is a systemic disease caused by various species of Plasmodium, transmitted through the bite of a female Anopheles mosquito. According to the World Health Organisation, there were 214 million cases of malaria worldwide in 2015. Nigeria’s burden of malaria is about 51million cases and 207,000 deaths annually, accounting for 60% of outpatient visits to hospitals, 11% of maternal mortality, and 30% of child mortality. The study aimed to compare RDT and microscopy in malaria diagnosis in a District Hospital in Enugu state, Southeast Nigeria. Methods: Blood samples of 300 suspected cases of acute malaria were tested for malaria parasite using RDT and microscopy simultaneously. Results: In 2017, the study found a malaria prevalence of 25% (46.2% in children, and 18.1% in adults) in Awgu. RDT was positive in 38% and microscopy in 70.3% of cases. Both RDT and microscopy were positive in 36.3%, negative in 28.3%, and discordant in 35.4%. Sensitivity of RDT was 50.7% (89.4% in children, and 25.6% in adults). RDT had a specificity of 100% (both children and adults), positive predictive value of 1 (both children and adults), and negative predictive value of 0.6 (0.5 in children, 0.6 in adults). Conclusions: RDT (SD Malaria Ag P. f) had more sensitivity in children (89.4%) than adults (25.6%), and the occurrence of false negative results was more in adults (46.8%) than children (9.5%). All negative RDT results need to be examined microscopically, to rule out false negative cases.